2018
DOI: 10.1002/jor.24020
|View full text |Cite
|
Sign up to set email alerts
|

Anterior longitudinal ligament in diffuse idiopathic skeletal hyperostosis: Ossified or displaced?

Abstract: Diffuse idiopathic skeletal hyperostosis (DISH) is often theorized to be an ossification of the anterior longitudinal ligament (ALL). Using computed tomography (CT) imaging and cryomacrotome sectioning, we investigated the spatial relationship between the ALL and newly formed bone in DISH to test this hypothesis. In the current study, four human cadaveric spines diagnosed with DISH using CT imaging were frozen and sectioned using a cryomacrotome. Photographs were obtained of the specimen at 125 µm intervals. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Some studies have reported mineralization of the anterior longitudinal ligament in DISH, 21,24,40 whereas others report that the anterior longitudinal ligament does not undergo mineralization 1,21 or that it is displaced by the formation of ectopic mineral structures. 26 In the current study, when present in the histological sections examined, the structure of the anterior longitudinal ligament was typically preserved. However, in a subset of specimens, we detected focal regions of dystrophic calcification within the ligament, resembling those detected within the annulus fibrosus.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Some studies have reported mineralization of the anterior longitudinal ligament in DISH, 21,24,40 whereas others report that the anterior longitudinal ligament does not undergo mineralization 1,21 or that it is displaced by the formation of ectopic mineral structures. 26 In the current study, when present in the histological sections examined, the structure of the anterior longitudinal ligament was typically preserved. However, in a subset of specimens, we detected focal regions of dystrophic calcification within the ligament, resembling those detected within the annulus fibrosus.…”
Section: Discussionmentioning
confidence: 59%
“…21,25 In contrast, recent studies in cadaveric tissues demonstrated that the anterior longitudinal ligament was morphologically normal in appearance and was displaced by ectopic mineral, but did not itself undergo aberrant mineralization. 26 Taken together, these findings underscore the need to identify and characterize the composition of the ectopic mineral formed in DISH, as well as the tissue types affected and associated cellular changes. The current study investigated these questions by combining radiological, histological, and physical analyses of human spine segments affected by DISH.…”
Section: Introductionmentioning
confidence: 76%